Completeness of Occupational History Taking Record for Out-Patients with Potential Work-Related Disorders at a University Hospital in Northeast of Thailand - Manotham, Manuchet; Chaiear, Naesinee; Yimtae, Kwanchanok; Thammaroj, Tala (Srinagarind Medical Journal, 2016)
Background and Objective: Patients’ occupation and job descriptions are important information for making appropriate diagnoses and patient care plans. As no Thai studies were found on this topic this research was designed to investigate the proportion of medical records with the completeness of occupational details recorded in the medical records of out-patients with potentially work-related injuries and/or occupational diseases. Materials and Methods: A cross-sectional descriptive survey was used to collect personal bio-data, and detailed occupational histories from 230 medical records of social security scheme patients at the Out-Patients Department at Srinagarind Hospital, Faculty of Medicine, Khon Kaen University. Results: Only 24.8 percent of physician recorded medical records included complete occupational histories. Although 45.7% noted patient’s occupation, only 24.3% of recorded occupations matched with the original occupations on the medical records. While only 44.3% presented job descriptions, a much higher proportion (89.6%) recorded occupational health hazards. Conclusion: This study confirms that rates of complete occupational health history taking record with potential work-related disorders by physicians were very low. Several factors may be relevant here; some data already recorded on medical record sheets before consultations take place, medical data collection form design, limited consultation time available for patient interactions, and/or less holistic and overly symptom/treatment focused approach to history taking and patient care. Complete occupational health history taking and recording is important for individual diagnosis and effective patient care plans and patients’ appropriate access to funding entitlements